2008
DOI: 10.1097/tp.0b013e3181874a36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Immunosuppressive Drugs On Purified Human B Cells: Evidence Supporting the Use of MMF and Rapamycin

Abstract: Our data show that MPA and rapamycin are capable of strongly inhibiting B cells responses. This provides a rationale for the use of both MPA and rapamycin to prevent or counteract humoral responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 46 publications
4
103
1
1
Order By: Relevance
“…5,6 However, those studies examined NHL risk in relation to agents received for maintenance immunosuppression on hospital discharge rather than on current receipt. However, receipt of mycophenolate, a potent suppressor of B-cell proliferation, 43 was associated with significantly reduced risk of NHL in 2 prior cohorts. 3,6 In the present study, no increase in NHL risk was observed with receipt of antiproliferative agents.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, those studies examined NHL risk in relation to agents received for maintenance immunosuppression on hospital discharge rather than on current receipt. However, receipt of mycophenolate, a potent suppressor of B-cell proliferation, 43 was associated with significantly reduced risk of NHL in 2 prior cohorts. 3,6 In the present study, no increase in NHL risk was observed with receipt of antiproliferative agents.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there have been some studies of the influence of CSA on B cells and the humoral response (92)(93)(94). CSA did not suppress Ab production in autoimmune diseases and transplantations (95)(96)(97), suggesting that the target mechanism in T cells is different from that in B cells; CSA targets calcium activation in T cells but may not affect that pathway in B cells (93,(98)(99)(100). However, we speculate that the mechanism by which CSA enhanced Ab production here may be indirect and via induction of Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…In an immunocompromised state, these patients tend to suffer from a myriad of different opportunistic infections that can be parasitic (57), fungal (58), bacterial (58), and viral (59) in origin. More recently, it has come to light that sirolimus, but not tacrolimus, inhibits B cell differentiation into antibody-producing plasma cells (60,61). Plasma cells produce the neutralizing antibodies against RSV that are critical for controlling and helping to clear virus infection.…”
Section: Increased Susceptibility To Rsv Infection Due To Pharmacologmentioning
confidence: 99%